2014
DOI: 10.1016/j.ijscr.2014.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Emergency thyroidectomy: Due to acute respiratory failure

Abstract: HighlightsCT scan has a great value for retrosternally extended giant goiter cases.If the general status of the patient prevents CT scan, bedside ultrasound can be used instead.Nasal awake intubiation is an appropriate choice for the patients with destructed trachea.Emergency thyroidectomy is a common option for the treatment of giant goiter causing airway obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…In the assessment of respiratory distress, stridor is a key sign that directs the physician to the upper airway. It is noteworthy that, in similarity to our case, other published cases in which goitre caused T2RF also do not mention stridor in the clinical presentation 4–6. This suggests a potentially dangerous pattern in which airflow limitation to critical levels causing hypercapnia may result in inaudible airway noises analogous to the scenario in which a non-wheezing silent chest can be mistaken for improved airflow in a hypercapnic asthmatic patient.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the assessment of respiratory distress, stridor is a key sign that directs the physician to the upper airway. It is noteworthy that, in similarity to our case, other published cases in which goitre caused T2RF also do not mention stridor in the clinical presentation 4–6. This suggests a potentially dangerous pattern in which airflow limitation to critical levels causing hypercapnia may result in inaudible airway noises analogous to the scenario in which a non-wheezing silent chest can be mistaken for improved airflow in a hypercapnic asthmatic patient.…”
Section: Discussionsupporting
confidence: 80%
“…The incidence of such presentations is not well documented although studies estimate this to be around 0.6–1.3% with a notable predilection for female patients although this may reflect increased baseline incidence of goitre in women 2 3. Presentation of goitre with decompensated type two respiratory failure (T2RF) is even rarer with only a few cases reported in the literature including reports by Bakkar et al and Bayhan et al 4 5…”
Section: Introductionmentioning
confidence: 99%
“…CT and MRI are preferred by many physicians and surgeons for evaluation of thyroid gland volume when US is considered insufficient due to different sizes or properties of the thyroid gland. Although it is neither cost- nor time-effective compared to US, the CT scan has great value in the preoperative evaluation of the patient and satisfactorily shows the thyroid size, substernal and mediastinal extension of the thyroid gland and its invasion into surrounding tissues and organs [4,24]. Previous studies have shown that, except for cases with substernal goiter, TV measured by US did not differ significantly from that measured by CT [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory distress caused by tracheal compression from the thyroid gland is an accepted indication for a thyroidectomy procedure [1,2,3,4]. Increased thyroid volume (TV) may cause respiratory symptoms due to continuous irritation of the upper airway [5], and with time, tracheal narrowing may lead to stridor and persistent hypoxia [6].…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Initial treatment used to be medical, and surgery is reserved for refractory cases, with urgent thyroidectomy only in cases of acute airway obstruction and recommended to be performed by an endocrine surgeon that can handle giant goiter complications, with nerve monitoring systems to minimize these damages. 3 The progression through the giant goiter should be considered and treated as soon as possible. The timing surgical intervention allow us to avoid morbidity and mortality associated, and for this reason it would be desirable to complete attention during the first stages of disease.…”
Section: Discussionmentioning
confidence: 99%